A Research on Data Dissemination and Topology Control for Wireless Sensor Networks - Mir, Zeeshan Hameed (The Graduate School, Ajou University, 2009)
The work in this dissertation spans several of the research challenges and issues in wireless sensor networks (WSNs). Sensors are battery driven thus energy conservation is critical for network lifetime longevity. However, network throughput and latency are equally important for many of the sensor network applications. The decision about how these nodes communicate has a significant impact on the energy, throughput and latency requirements of a specific application. Specially, particular network architectures with mobile nodes and low-power image sensors poses several new challenges for control protocols (such as channel access and routing) design and development. Moreover, the efficiency of a sensor network depends not only on its control protocols, but also on its topology. Topology control has been proved to be an efficient method for reducing energy consumption and enhancing the network capacity. In such protocols, sensor nodes collaborate to optimize the choice of their transmit power level in order to generate a final network topology with the desired properties. The first part of the dissertation is a bipartite that addresses two different research problems. (1) Data Dissemination in mobile sensor networks; and (2) An enhancement to IEEE 802.15.4 protocol to support multimedia services in sensor networks. Each of problems is presented in an independent chapter. In the first chapter of this part, we present a data dissemination scheme that exploits Quadtree-based successive partitioning of sensor network space to calculate a set of rendezvous points. A common hierarchy of rendezvous nodes is then constructed to provide more efficient routing among multiple mobile stimuli and sink nodes. Through extensive simulation based studies we have shown that by making data forwarding independent of the current mobile stimuli location we are able to conserve significant amount of energy. Moreover, the proposed scheme minimizes communication overhead/delay associated with tracking sink mobility, as well. The main contributions of the second chapter are design and implementation of TEA-15.4 (short for Traffic and Energy-Aware IEEE 802.15.4), an enhancement to the IEEE 802.15.4 MAC protocol. Our scheme design exploits the information on data traffic to adapt the active period in Beacon-Enabled mode of the protocol. In order to convey data traffic information to the Wireless Personal Area Network (WPAN) coordinator we provide two traffic indication techniques. Both of these techniques are compatible with the original IEEE 802.15.4 standard i.e., the traffic indication process works without introducing any new control frame. Through extensive simulations and testbed experiments, we show that TEA.15.4 not only provides sufficient throughput to support multimedia communication, but also offers lower energy consumption for the sensing devices. The second part of this dissertation involves the design and evaluation of two neighbor-based topology control algorithms for sensor networks. Both algorithms concentrate on the improvements of energy efficiency of the whole network through optimization of number of neighbors of each node. Lower message complexity makes these schemes scalable and suitable for energy constrained sensor networks. In the first algorithm, we ensure fully-connected network topology with significantly lesser energy cost and neighborhood size than the previous studies. We also proposed a neighbor-based mechanism to support a mobile sink and show that sink mobility over the topology controlled network has negligible effect on the network performance. While previous research for topology control in wireless ad hoc networks emphasized on finding an optimal transmission range for each node with minimal energy cost and network-wide connectivity; little work is done on generating topologies that can be tuned to favor certain data traffic models in WSNs at the same time as giving good performance for a wide array for design goals. We presented an efficient, coloring algorithm that construct single network topology structure at various levels of details. The performance knob ? is employed that offers trade-off among several conflicting design goals such connectivity, minimum energy cost, path hop count and higher spatial reuse or lower interference by means of lower nodal degree.
학위논문(박사)--아주대학교 정보통신전문대학원 :정보통신공학과,2009. 2